Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Courthouse staff catch cut ribbon with Fresno County Bar Association President G. Dana French and Fresno County Board of Supervisors Chair Vernon Conrad